2014
DOI: 10.1186/1471-2334-14-s1-s1
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the immunology of tuberculosis: will we ever unravel the skein?

Abstract: Many and large dumps exist in our knowledge about Mycobacterium tuberculosis infection and disease in infants and children. We still do not understand why some individuals do acquire and others do not acquire the infection in the presence of the same risk factors. We do not understand why some individuals convert from latent to active tuberculosis and why other individuals convert from active to inactive tuberculosis even without treatment.As a matter of fact the immune system mounts a bouncing, robust and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…de Martino et al [7] describe the initial combat of TB once it invades the host using the quote: "All is decided the first day, which gets the longest day". Once the bacterium M. tuberculosis (MTB) is inhaled via droplets spread through person-to-person contact, macrophages can phagocytose and kill the bacilli.…”
Section: Pathogenesis and Immune Response: The Interactions Between Mmentioning
confidence: 99%
See 3 more Smart Citations
“…de Martino et al [7] describe the initial combat of TB once it invades the host using the quote: "All is decided the first day, which gets the longest day". Once the bacterium M. tuberculosis (MTB) is inhaled via droplets spread through person-to-person contact, macrophages can phagocytose and kill the bacilli.…”
Section: Pathogenesis and Immune Response: The Interactions Between Mmentioning
confidence: 99%
“…However, if the bacilli are not killed, during that initial interaction, they can proliferate within dendritic cells and alveolar macrophages at a rapid rate, signaling the production of IL-1-a, IL-1b, and other host proinflammatory cytokines. This response is mediated by pattern recognition receptors (PRRs) [7,11] expressed by macrophages and dendritic cells that recognize pathogen-associated molecular patterns (PAMPS) expressed on MTB [11]. Toll-like receptors (TLRs) help uptake MTB, which induces an intracellular signaling cascade to produce the cytokines.…”
Section: Pathogenesis and Immune Response: The Interactions Between Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Most research has been conducted in the host defense against M. tuberculosis, which shows a prominent role for interleukin-12 (IL-12), interferon-c (IFN-c), and tumor necrosis factor-a. These cytokines are responsible for promoting a Type 1 T helper cell (Th-1) response, activating antigen presentation, and phagocytosis [10]. CCR4 is normally associated with a Th-2 immune response, although recent research showed a comparable Th-1 and Th-2 granulomatous response after the introduction of Mycobacterium bovis antigen-coated agarose beads in the lungs of mice.…”
Section: Discussionmentioning
confidence: 99%